ANALISIS PRODUKSI TANAMAN GAMBAS (Luffa acutangula L.) VARIETAS ANGGUN F1 DENGAN APLIKASI PETROGANIK DAN POC NASA - Dwi Handika; Nunuk Helilusiatiningsih; Tarwa Mustopa (AGROTEK: Jurnal Ilmiah Ilmu Pertanian, 2023)
Gambas contain vitamins  A, B, C,  and nutrition Ca, P, Fe, and fiber. The provision of nutrients from inorganic species has an effect that can lead to a decrease in plant fertility, increasing dependence on an ongoing basis, efforts to improve agricultural cultivation techniques, and organic fertilization. Research in Purworejo Village, Tulungagung. The method used was Randomized Block Design, with two factors. Factor (I) is Petroganic fertilizer with three levels (P), and factor (II) is the concentration of POC Nasa with three levels denoted (N) 3 repetitions so that there are 27 treatment plots. The results showed that there was no interaction between Petroganic administration and Nasa LOF, significant effect was with the addition of 12 tons/ha (P3) of Petroganic fertilizer had the highest average value of 792,750 gr. on the weight of the gambas. With the addition of 8ml/L (N3) Nasa LOF, the highest fruit weight was 778.17 gr, fruit length was 35.35 cm.